Experiences, awareness, perceptions and attitudes of women and girls towards menstrual hygiene management and safe menstrual products in Pakistan - Malik, Madeeha; Hashmi, Ayisha; Hussain, Azhar; Khan, Waleed; Jahangir, Nabia; Malik, Anam; Ansari, Naima (Frontiers in Public Health, 2023)
Background: The taboo of menstruation, lack of discussion on puberty, misinformation and poor awareness on menstrual hygiene management and limited access to safe menstrual products can negatively impact the physical and mental health of women and girls residing in low middle income countries. Aim: The aim of the study was to explore the experiences, awareness, perceptions and attitudes of women and girls towards menstrual hygiene management in Pakistan. Moreover, the study also assessed consumer satisfaction towards locally manufactured organic menstrual products. Methods: A descriptive cross-sectional study design was used with a sample of 400 women and girls selected through convenience sampling from high schools, universities, outpatient department and gynaecological clinics located in two cities i.e. Islamabad and Rawalpindi, Pakistan. A pre-structured questionnaire was used to explore experiences, awareness, perceptions and attitudes of women and girls towards menstrual hygiene management. Moreover, each respondent was provided with sample of locally designed and manufactured organic menstrual hygiene & wellness kit by a group of women researchers named “Fempure” including organic sanitary pads, feminine wellness mist and feminine wellness wash. The respondents were asked to use the products and a telephonic follow-up was conducted to assess consumer satisfaction for the products after a period of one month. Data was analysed statistically using SPSS 21. Results: The results of the study reported that 86.2% (n=345) of the respondents had normal periods. Out of 400 respondents, 58.5% (n=234) knew about any health conditions related to abnormal menstrual cycle while 88.3% (n=353) were aware of female menstrual hygiene. Majority of the respondents 78.7 % (n=315) felt ashamed while buying sanitary pads. Out of 400 respondents, 5.4% (n=22) were interested in getting awareness regarding menstrual hygiene. The results of the study showed that all the respondents (100%, n=400) were satisfied with fempure organic menstrual products. Conclusion: The study concluded that majority of women and girls faced menstrual hygiene issues during and after the cycle and were eager to receive information on MHM and use organic rash free menstrual wellness products which could be ordered via mobile app. The respondents were satisfied after the use of organic menstrual products.